Facile Hydrothermal Synthesis of Tin Doped Copper Bismuthate for the Real Time Electrochemical Determination of Chloramphenicol in Real Samples. Issue 5 (1st May 2022) - Kaleeswarran, Periyannan; Nataraj, Nandini; Chen, Tse-Wei; Chen, Shen-Ming; Arumugam, Ayyakannu
Abstract : In the present work, we investigated a one-step hydrothermal synthesis of copper bismuthate (CBO) and Sn doped (SCBO). The properties of CBO have been enriched by doping of Sn, which has been inclined to modify screen printed carbon electrode for the electrochemical determination of chloramphenicol (CMP). The dopant Sn with CBO was varied [(SCBO-1), (SCBO-5), (SCBO-10)] with comparison analysis done to choose highly conducting composite. The doping of Sn over CBO is highly a new strategy in detecting CMP which showed improved electrical conductivity with the dopant variation. Among, the different dopant variations, SCBO-5 demonstrated enhanced electrochemical response towards CMP when compared with the other dopant variations. Highly enriched actives sites at SCBO-5/SPCE resulted with a low detection limit of 0.007 μ M and a sensitivity about 5.7 μ A μ M −1 cm −2 with linear range of 0.09 μ M to 475.73 μ M. The decrease in particle size with improved surface area deliberately influenced the detection range and the sensitivity with improved electrochemical performances. The fabricated hybrid material with cost effective materials is highly significant over other high cost preparation materials. The substitution of Sn substantially increases both the electrical conductivity and electro catalytic activity of CBO which is strongly agreed by the electrochemical performance.